Design And Development Of Presence System System Using Rfid Based On Raspberry Pi - Eni Dwi Wardihani (JAICT, 2017)
Presence of students of the Master of Telecommunications Engineering Study Program majoring in Electrical Engineering Semarang State Polytechnic is currently still managed and carried out manually. This does not rule out the possibility of errors in managing data attendance and cheating students in faking their presence, and also with the development of science and technology that is currently completely automated. From this background, it was made the Presence Using RFID Based Raspberry Pi System where the PBM became Admin to be able to access all the attendance data of the S2 Telecommunications Engineering students. Student attendance recording is done by PBM by opening a MySQL database that has been created and stored, then processed and adjusted to existing student data as student ID. The end result obtained is a tool and system that are integrated automatically and also precisely, so that students are required to arrive on time so that they do not get the Compensation if they have passed the deadline and PBM admin can manage the recapitulation data through the website including student data, data lecturer, course data, room data, lecture schedule, attendance activities, and print reports in PDF format. The trial was carried out in the Computer Lab of the Semarang State Polytechnic Applied Science Master. The conclusion is that this tool and system is able to educate students to come and have a scheduled presence and can also record attendance automatically.